Penerapan Telenursing pada Klien dengan Skizoferenia - Anisa Yulvi Azni; Sukihananto (Jurnal Kesehatan, 2020)
ABSTRACT Background: Advances in the technological era affect aspects of life, especially in the field of Mental Nursing. The technology commonly used in schizophrenia patients is telenursing using telephone-based practices. Telenursing is a combination of telecommunication and nursing services where there is a physical distance between nurses and patients. Purpose: to describe the application of telenursing in patientss with schizophrenia. Methods: This study uses a literature review from an online database UI: Scopus, ProQuest, ScienceDirect (2015-2020) using the keywords telenursing, telehealth, telephone nursing, schizophrenia. Results: The search results showed that 10 journals were selected and to be reviewed and it was found that telenursing can improve treatment adherence for schizophrenia patients. Patients and nurses both receive and provide efficient and effective services in reducing the number of non-adherence to taking medication in schizopherenia patients. Conclusion: Telenursing provides benefits for schizophrenia patients so as not to experience withdrawal.